2019
DOI: 10.1093/nsr/nwz198
|View full text |Cite
|
Sign up to set email alerts
|

Large dipole moment induced efficient bismuth chromate photocatalysts for wide-spectrum driven water oxidation and complete mineralization of pollutants

Abstract: Herein, a wide-spectrum (∼678 nm) responsive Bi8(CrO4)O11 photocatalyst with a theoretical solar spectrum efficiency of 42.0% was successfully constructed. Bi8(CrO4)O11 showed highly efficient and stable photocatalytic water oxidation activity with a notable apparent quantum efficiency of 2.87% (420 nm), superior to many reported wide-spectrum driven photocatalysts. Most remarkably, its strong oxidation ability also enables the simultaneous degradation and complete mineralization for phenol, and its excellent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…À anions on Ni 35 /NC-sd catalyst, the surface charges of various Ni x /NCsd samples are carefully analyzed using Kelvin probe force microscopy techniques (Figure 3 a). [10] With similar heights (Figure S18), the Ni 35 /NC-sd with more Ni/NC heterojunctions integrated inside exhibits more negative the contact potential difference (DV) between the Si substrate and the sample (À0.148 V), which is two times of the value of Ni 14 /NC-sd sample (Figure 3 b). It is reasonable that merging more Ni/ NC heterojunctions into one sample enlarges the negatively charged surface field located on the carbon support via accepting more electrons from the Ni nanoparticle-based electron donors as already demonstrated in Figure 1 f and 2 c.…”
mentioning
confidence: 85%
“…À anions on Ni 35 /NC-sd catalyst, the surface charges of various Ni x /NCsd samples are carefully analyzed using Kelvin probe force microscopy techniques (Figure 3 a). [10] With similar heights (Figure S18), the Ni 35 /NC-sd with more Ni/NC heterojunctions integrated inside exhibits more negative the contact potential difference (DV) between the Si substrate and the sample (À0.148 V), which is two times of the value of Ni 14 /NC-sd sample (Figure 3 b). It is reasonable that merging more Ni/ NC heterojunctions into one sample enlarges the negatively charged surface field located on the carbon support via accepting more electrons from the Ni nanoparticle-based electron donors as already demonstrated in Figure 1 f and 2 c.…”
mentioning
confidence: 85%
“…Our group found that in the bismuth iodide series photocatalyst, the reduction in the content of iodine element that contributes to the valence band maximum (VBM) composition significantly shifts the position of the VBM, thereby obtaining enhanced oxidation capacity 16 . In addition, we also found that the contribution of chromium element make the VB and CB positions of Bi 8 (CrO 4 )O 11 move down directly promote the oxidation capacity and narrow the band gap, thereby completely mineralized phenol into CO2 and response wide spectral absorption 77 …”
Section: Control Factors Of Surface Hybridization For Enhancing Reaction Activitymentioning
confidence: 73%
“…16 In addition, we also found that the contribution of chromium element make the VB and CB positions of Bi 8 (CrO 4 )O 11 move down directly promote the oxidation capacity and narrow the band gap, thereby completely mineralized phenol into CO2 and response wide spectral absorption. 77 From macro perspective, one considerable factor is the appropriate size of the inorganic material. If the particle size is too large, the charge separation efficiency will be reduced.…”
Section: Intrinsic Properties Of Photocatalystmentioning
confidence: 99%
“…Since visible light accounts for ~ 45% of the total radiant energy of sunlight, a wide-spectrum response is particularly important 31 . Contributed by the π-π accumulation induced extended conjugated electron cloud, the edge of the intrinsic absorption band of PTCDA covers the entire visible range of 630nm, further calculating the bandgap of 1.97ev, the position of CB and VB is -0.33V and 1.64V, respectively (Figure S10).…”
Section: Resultsmentioning
confidence: 99%